A sustainable approach to learning: Enhancing creative thinking skills through creative problem solving in green schools - Anisa O. S. Pratama; Akbar Handoko; Eko Kuswanto; Daffa Rahmanda Asnawi (Assimilation)
This research aims to analyse the influence of the Creative Problem-Solving learning model on the creative thinking skills of class XII high school students. This research uses a quantitative approach with a quasi-experimental design, specifically the matched only pre-test post-test control group design. The population in this study consisted of 167 students. The research sample was obtained using the cluster random sampling technique, resulting in an experimental class of 34 students and a control class of 34 students. The instruments used were tests, questionnaires, observation sheets, and documentation. The collected data was analysed using the MANOVA test. The results show that the N-Gain value for creative thinking skills in the experimental class is higher than in the control class, specifically 0.58 > 0.36. Therefore, it can be concluded that there is a significant influence of using the Creative Problem-Solving learning model on improving the creative thinking skills of class XII high school students.